2021
DOI: 10.1021/acsami.1c21924
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Microbubbles Mediated Sonosensitizer and Antibody Co-delivery for Highly Efficient Synergistic Therapy on HER2-Positive Gastric Cancer

Abstract: Trastuzumab combined with chemotherapy is the first-line treatment for advanced HER2-positive gastric cancer, but it still suffers from limited therapeutic efficiency and serious side effects, which are usually due to the poor delivery efficiency and the drug resistance of tumor cells to the chemotherapeutic drugs. Herein, a type of ultrasound microbubble for simultaneous delivery of sonosensitizers and therapeutic antibodies to achieve targeting combination of sonodynamic therapy and antibody therapy of HER2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 42 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…Briefly, 0.6 mg DSPC and 0.2 mg DSPE-PEG2000-NHS (with molar ratio of about 9:1) were used to prepare the lipid nanoparticles, followed by incubation with 0.2 mg targeted peptide C12 for 1 hour at 30°C (molar ratio of DSPE-PEG2000-NHS/C12 peptide =1:2). Then, the formed targeted C12-lipid nanoparticles were dialyzed to remove unconnected peptide and used to prepare Gal-3-C12@lipo MBs by the same way of inflating and shaking (29).…”
Section: Synthesis Of Lipo Mbs and Gal-3-c12@lipo Mbsmentioning
confidence: 99%
“…Briefly, 0.6 mg DSPC and 0.2 mg DSPE-PEG2000-NHS (with molar ratio of about 9:1) were used to prepare the lipid nanoparticles, followed by incubation with 0.2 mg targeted peptide C12 for 1 hour at 30°C (molar ratio of DSPE-PEG2000-NHS/C12 peptide =1:2). Then, the formed targeted C12-lipid nanoparticles were dialyzed to remove unconnected peptide and used to prepare Gal-3-C12@lipo MBs by the same way of inflating and shaking (29).…”
Section: Synthesis Of Lipo Mbs and Gal-3-c12@lipo Mbsmentioning
confidence: 99%
“…In addition, the approach was more targeted than epirubicin therapy alone and was associated with reduced cardiac toxicity in mice models. Sun et al (20) constructed an ultrasonic MB loaded with trastuzumab coupled with acoustic sensitizer nanoparticles. They found that the delivery and treatment efficiency with nanoparticles was improved with UTMD and successfully inhibited the proliferation of tumor cells, achieving a targeted combination of sonodynamic therapy and antibody therapy with nanoparticles for treating HER2positive gastric cancer (Figure 4).…”
Section: Utmd-mediated Antibody Immunotherapymentioning
confidence: 99%
“…International Journal of Nanomedicine 2022:17 3990 systemic toxicity and side effects, 25,26 and to evaluate synergistic antitumor mechanisms in the immune responses of ultrasound-mediated PD-L1 mAb/DOX-NBs on HCC xenografts.…”
Section: Dovepressmentioning
confidence: 99%
“…Thus, in this study, the method of ultrasound-triggered NBs drug delivery targeting was implemented to improve local drug concentrations and limit drug uptake by normal cells, thus significantly enhancing therapeutic effects and reducing systemic toxicity and side effects, 25 , 26 and to evaluate synergistic antitumor mechanisms in the immune responses of ultrasound-mediated PD-L1 mAb/DOX-NBs on HCC xenografts.…”
Section: Introductionmentioning
confidence: 99%